TINDAK TUTUR REPRESENTATIF DALAM STATUS FACEBOOK - Suyalik Maysaroh; Mangatur Sinaga; Hasnah Faizah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study examines the act of representative speech in facebook status. This study aims to describe the act of representative speech in facebook status. This research is descriptive-qualitative research. This research data is data taken from the status that contains representative speech in the facebook homepage. Instruments in this research is screenshoot (data recording) facebook status then transcribed and typed compiled Data collection is done by documentation technique. Data were taken as many as 150 data during January 2017. Data were analyzed by qualitative descriptive method. From the data obtained found sebnayak 86 data included into the act of representative speech. The type of representative speech act consists of acts of speech representatives stated, acts of speech representatives suggest, acts of speech representatives tells, acts of speech representative complain, acts of representative speech demands and acts speech representative report. Of the seven types of representative speech acts in facebook status only found the five types of speech acts are representative of stating, telling, suggesting, boasting and complaining.Keywords: Speech, Representative, Facebook.